Risk characteristics of the combined geographic atrophy and choroidal neovascularisation phenotype in age-related macular degeneration. Issue 12 (4th August 2014) - Saade, Celine; Ganti, Bhaskar; Marmor, Michael; Freund, K Bailey; Smith, R Theodore
Abstract : Aim: To investigate the risk characteristics of the combined geographic atrophy (GA) and choroidal neovascularisation (CNV) phenotype of age-related macular degeneration (AMD) compared to GA or CNV. Methods: Patients with advanced AMD were identified and divided into three groups using multimodal imaging: patients with GA in at least one eye, patients with CNV in at least one eye, and patients with simultaneous GA and CNV in at least one eye. Epidemiologic and clinical factors were gathered from patient questionnaires. Genotypes for age-related maculopathy susceptibility 2 ( ARMS2 ) and complement factor H ( CFH ) were determined. Results: 42 patients with GA or CNV, and 16 patients with combined GA/CNV were identified. Patients with the combined phenotype were older (86.4 vs 81.8 years, p=0.049), and had a higher prevalence of advanced AMD in the fellow eye (81.3% vs 31.0%, p<0.001). CFH and ARMS2 risk alleles were not associated with the combined phenotype. Conclusions: The combined GA/CNV phenotype has similar epidemiologic, clinical, and genetic features as GA and CNV, but occurs at an older age and is more associated with advanced AMD in the fellow eye, suggesting that all these phenotypes are part of the same spectrum of disease and that the combined phenotype represents an even more advanced form of AMD than either GA or CNV.